The lost daughter eaudiobook - Ferrante, Elena (Blackstone Audio, Inc., and Buck 50 Productions, LLC, 2015)
An edgy tale of mixed feelings and motherhood by the New York Times bestselling author of My Brilliant Friend Leda, a middle-aged divorcée, is alone for the first time in years after her two adult daughters leave home to live with their father in Toronto. Enjoying an unexpected sense of liberty, she heads to the Ionian coast for a vacation. But she soon finds herself intrigued by Nina, a young mother on the beach, eventually striking up a conversation with her. After Nina confides a dark secret, one seemingly trivial occurrence leads to events that could destroy Nina's family in this "arresting" (Publishers Weekly) novel by the author of the New York Times bestselling Neapolitan Novels, which have sold millions of copies and been adapted into an HBO series.